Genetic changes caused by restocking and hydroelectric dams in demographically bottlenecked brown trout in a transnational subarctic riverine system - Klütsch, Cornelya F. C. (Ecol Evol, 2019)
Habitat discontinuity, anthropogenic disturbance, and overharvesting have led to population fragmentation and decline worldwide. Preservation of remaining natural genetic diversity is crucial to avoid continued genetic erosion. Brown trout (Salmo trutta L.) is an ideal model species for studying anthropogenic influences on genetic integrity, as it has experienced significant genetic alterations throughout its natural distribution range due to habitat fragmentation, overexploitation, translocations, and stocking. The Pasvik River is a subarctic riverine system shared between Norway, Russia, and Finland, subdivided by seven hydroelectric power dams that destroyed about 70% of natural spawning and nursing areas. Stocking is applied in certain river parts to support the natural brown trout population. Adjacent river segments with different management strategies (stocked vs. not stocked) facilitated the simultaneous assessment of genetic impacts of dams and stocking based on analyses of 16 short tandem repeat loci. Dams were expected to increase genetic differentiation between and reduce genetic diversity within river sections. Contrastingly, stocking was predicted to promote genetic homogenization and diversity, but also potentially lead to loss of private alleles and to genetic erosion. Our results showed comparatively low heterozygosity and clear genetic differentiation between adjacent sections in nonstocked river parts, indicating that dams prevent migration and contribute to genetic isolation and loss of genetic diversity. Furthermore, genetic differentiation was low and heterozygosity relatively high across stocked sections. However, in stocked river sections, we found signatures of recent bottlenecks and reductions in private alleles, indicating that only a subset of individuals contributes to reproduction, potentially leading to divergence away from the natural genetic state. Taken together, these results indicate that stocking counteracts the negative fragmentation effects of dams, but also that stocking practices should be planned carefully in order to ensure long‐term preservation of natural genetic diversity and integrity in brown trout and other species in regulated river systems.